2016
DOI: 10.7759/cureus.882
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Study of Automatic Brain Metastases Planning in Comparison with Conventional Multi-Isocenter Dynamic Conformal Arc Therapy and Gamma Knife Radiosurgery for Multiple Brain Metastases

Abstract: ObjectiveThe efficacy of stereotactic radiosurgery (SRS) using Gamma Knife (GK) (Elekta, Tokyo) is well known. Recently, Automatic Brain Metastases Planning (ABMP) Element (BrainLAB, Tokyo) for a LINAC-based radiation system was commercially released. It covers multiple off-isocenter targets simultaneously inside a multi-leaf collimator field and enables SRS / stereotactic radiotherapy (SRT) with a single group of LINAC-based dynamic conformal multi-arcs (DCA) for multiple brain metastases. In this study, dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…With the recent introduction of commercial single‐isocenter planning algorithms for simultaneously treating multiple brain metastases, either using automated dynamic conformal arcs or automated VMAT, more dosimetric comparison to GK is required. These studies have already demonstrated a reduction in monitor units compared with conventional VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent introduction of commercial single‐isocenter planning algorithms for simultaneously treating multiple brain metastases, either using automated dynamic conformal arcs or automated VMAT, more dosimetric comparison to GK is required. These studies have already demonstrated a reduction in monitor units compared with conventional VMAT.…”
Section: Discussionmentioning
confidence: 99%
“…per lesion makes linac-based SRS/FSRT unsuitable for patients with ≥5 BM. To support the use of SRS/FSRT in patients with several BM, mono-isocenter volumetric modulated arc therapy (VMAT) approaches with multiple non-coplanar arcs have been proposed [ 11 14 ], with the potential to treat multiple BM within a typical time slot (about 20 min.) thanks to the use of one IGRT session.…”
Section: Introductionmentioning
confidence: 99%
“…The common goal of all these linac SRS techniques is to use a single isocenter to treat all of the metastases simultaneously, in order to avoid prohibitively long treatments with multiple isocenters and thereby improve patient comfort and throughput. The most current single isocenter linac-based SRS options include multi-aperture dynamic conformal arcs on a linac (3032) (BrainLab Elements™ v1.5, Munich, Germany), volumetric arc therapy (VMAT) calculated with the conventional optimizer (3343) (Varian Medical Systems, Palo Alto, CA) or VMAT delivery calculated with the newer Varian HyperArc solution (4447).…”
Section: Introductionmentioning
confidence: 99%